Α-Cyperone inhibits LPS-induced inflammation in BV-2 cells through activation of Akt/Nrf2/HO-1 and suppression of the NF-κB pathway. Issue 5 (18th April 2018) - Huang, Bingxu; He, Dewei; Chen, Guangxin; Ran, Xin; Guo, Wenjin; Kan, Xingchi; Wang, Wei; Liu, Dianfeng; Fu, Shoupeng; Liu, Juxiong
Abstract : Accumulating evidence has shown that activated microglia cause inflammatory immune response, which could lead to neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease. Abstract : Accumulating evidence has shown that activated microglia cause inflammatory immune response, which could lead to neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease. α-Cyperone, one of the main ingredients of Cyperus rotundus oil, has been reported to possess anti-inflammatory activity in activated macrophages. In this study, we found that α-cyperone markedly decreased the production of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β) in LPS-induced BV-2 cells. Moreover, α-cyperone inhibited NF-κB activation and enhanced heme oxygenase-1 (HO-1), nuclear factor-E2-related factor 2 (Nrf2) and Akt expression. Furthermore, we found that α-cyperone could upregulate HO-1 expression and enhance nuclear translocation of Nrf2 via activating the Akt signaling pathway, and inhibition of Akt, Nrf2 or HO-1 attenuated LPS-induced expression of proinflammatory cytokines in BV-2 cells. Moreover, the toxicities of conditioned medium from activated microglia toward dopaminergic neuronal SH-SY5Y cells and hippocampal neuronal HT22 cells were significantly inhibited by pretreatment with α-cyperone. Taken together, our results indicate that α-cyperone exerts neuroprotective effects by inhibiting the production of inflammatory cytokines in BV-2 cells through activating Akt/Nrf2/HO-1 and suppressing the NF-κB pathway.